Shared intentionality shapes humans' technical know-how. (10th August 2020) - Moll, Henrike; Nichols, Ryan; Pueschel, Ellyn
Abstract: Osiurak and Reynaud argue that cumulative technological culture is made possible by a "non-social cognitive structure " (sect. 1, para. 1) and they offer an account that aims "to escape from the social dimension" (sect. 1, para. 2) of human cognition. We challenge their position by arguing that human technical rationality is unintelligible outside of our species' uniquely social form of life, which is defined by shared intentionality (Kern & Moll 2017, Philosophical Psychology 30 (3):319–37; Tomasello 2019a, Becoming human: A theory of ontogeny . Cambridge, MA: Belknap Press).